(untitled) (Asian Education Studies, 2017)
Since becoming an independent subject, psychology has portrayed itself as a strict science on the way to the development of natural science. Because of breaking away from the social cultural and historical background of human life, scientific psychology is being questioned. In the doubt, non scientific psychology which is closer to social life and can adapt to the human need emerges as the times require. Performance psychology developing from social therapy insists on a new cultural-performatory approach to understanding human life, making psychology research return to life and helping people to restart their development. Non-epistemology, non-diagnosis and non-adaptability are the essential embodiment of performing psychology from the natural science to the post-modern humanities.